TEST SYSTEM FOR EVALUATION OF THE INFLUENCE OF THE BIOLOGICAL ACTIVITY OF SUBSTANCES ON THE SIGNAL SYSTEM OF NF-κB: FOCUS ON THE DERIVATIVES OF 3-HYDROXYPYRIDINE - Sophiya Ya. Skachilova; Vera Ragulina; Darya Kostina; Youri Burda (Research Results in Pharmacology, 2017)
Introduction: The nuclear factor kappa B is one of the most promising targets for the development of innovative medicines in the development of modern pharmacology and the formation of the concept of targeted therapy. Potential candidates modulating the activity of this transcription factor are 3-hydroxypyridine derivatives. Materials and methods: At the first stage of our study, 11 pharmacological agents-inhibitors of NF-κB in vitro were screened with an estimate of the activity of the p65 subunit in mononuclear cells stimulated by bacterial lipopolysaccharide. The most active substances were: mexidol, ethoxidol and the agent under the code XS-9. Further inhibitory activity against NF-κB pharmacological agents was studied on 4 models: L-NAME-induced endothelial dysfunction, staphylococcal sepsis, acute toxic liver damage and acute pancreatitis. Main part: On L-NAME-induced endothelial dysfunction, the inhibitory activity of the compounds, was arranged in the following order: XS-9 → ethoxydol → mexidol. With staphylococcal sepsis and acute toxic liver damage, the compounds XS-9 and ethoxidol demonstrated the same effectiveness with respect to the modulation of the activity of the NF-κB signaling system, mexidol had the least effect. On the model of acute pancreatitis, the inhibitory activity of the compounds, was arranged in the following order: ethoxidol → XS-9 → mexidol. Conclusion: Thus, 3-hydroxypyridine derivatives showed a significant activity on the NF-κB signaling system, both in the screening method and in various models leading to its pathological activation. In this connection, it is necessary to study further the mechanisms of action of these pharmacological substances and to confirm their effectiveness in the presented models in in vivo experiments.